Sensory nerves mediate spontaneous behaviors in addition to inflammation in a murine model of psoriasis. Issue 2 (11th September 2018) - Kodji, Xenia; Arkless, Kate L.; Kee, Zizheng; Cleary, Simon J.; Aubdool, Aisah A.; Evans, Elizabeth; Caton, Paul; Pitchford, Simon C.; Brain, Susan D.
ABSTRACT: Psoriasis is characterized by keratinocyte hyperproliferation, erythema, as well as a form of pruritus, involving cutaneous discomfort. There is evidence from both clinical and murine models of psoriasis that chemical or surgical depletion of small‐diameter sensory nerves/nociceptors benefits the condition, but the mechanisms are unclear. Hence, we aimed to understand the involvement of sensory nerve mediators with a murine model of psoriasis and associated spontaneous behaviors, indicative of cutaneous discomfort. We have established an Aldara model of psoriasis in mice and chemically depleted the small‐diameter nociceptors in a selective manner. The spontaneous behaviors, in addition to the erythema and skin pathology, were markedly improved. Attenuated inflammation was associated with reduced dermal macrophage influx and production of reactive oxygen/nitrogen species (peroxynitrite and protein nitrosylation). Subsequently, this directly influenced observed behavioral responses. However, the blockade of common sensory neurogenic mechanisms for transient receptor potential (TRP)V1, TRPA1, and neuropeptides (substance P and calcitonin gene‐related peptide) using genetic and pharmacological approaches inhibited the behaviors but not the inflammation. Thus, a critical role of the established sensory TRP‐neuropeptide pathway in influencing cutaneous discomfort is revealed, indicating the therapeutic potential of agents that block that pathway. The ongoing inflammation is mediated by a distinct sensory pathway involving macrophage activation.—Kodji, X., Arkless, K. L., Kee, Z., Cleary, S. J., Aubdool, A. A., Evans, E., Caton, P., Pitchford, S. C., Brain, S. D. Sensory nerves mediate spontaneous behaviors in addition to inflammation in a murine model of psoriasis. FASEB J. 33, 1578–1594 (2019). www.fasebj.org